TREM‐1 deficiency attenuates the inflammatory responses in LPS‐induced murine endometritis. Issue 6 (31st July 2019) - Zhu, Hongmei; Li, Wenke; Wang, Zhuole; Chen, Jianguo; Ding, Mingxing; Han, Li
Summary: Endometritis, which is usually caused by bacterial infection, is characterized by high levels of pro‐inflammatory cytokines and a high infertility rate. Triggering receptor expressed on myeloid cells‐1 (TREM‐1) has been recognized as a potent amplifier of inflammatory reactions. Studies have demonstrated reduced inflammatory responses and mortality rates of animals with bacterial infection due to the blocking of TREM‐1 expression. However, whether TREM‐1 deficiency could alleviate the inflammatory reaction in bacterial endometritis is still unclear. Here, TREM‐1 knock‐out ( Trem‐1 −/− ) mice were used to inhibit TREM‐1 signalling to evaluate its role in inflammatory reactions after a highly pathogenic LPS infection in mice uteri. The results demonstrated that TREM‐1 deficiency attenuated the inflammation in mice uteri; markedly reduced the number of polymorphonuclear neutrophils; and suppressed interleukin‐1β (IL‐1β), IL‐6, and tumour necrosis factor‐α (TNF‐α) concentrations in serum as well as their production in inflamed uteri after LPS stimulation. Our results illustrate an anticipated pathogenic impact of TREM‐1 on endometritis during LPS infection and indicate that blocking of TREM‐1 in LPS‐induced endometritis holds considerable promise for blunting excessive inflammation. Abstract : Triggering receptor expressed on myeloid cells‐1 (TREM‐1) has been recognized as a potent amplifier of inflammatory reactions. The current study have explored the relationship of Trem‐1 and LPS‐induced endometritis. The results demonstrate that TREM‐1 deficiency attenuated the inflammation and reduced the number of polymorphonuclear neutrophils in uteri, probably by suppressing the proinflammatory cytokines of interleukin‐1β (IL‐1β), IL‐6, and tumor necrosis factor‐α (TNF‐α) expression after LPS stimulation.